Cis/transgene optimization : systematic discovery of novel gene expression elements using bioinformatics and computational biology approaches /: systematic discovery of novel gene expression elements using bioinformatics and computational biology approaches. ([2018]) - Kadkhodaei, Saeid
No abstract available